Toward quantitative SERS detection in low analyte concentration by investigating the immersion volume and time of SERS substrate in analyte solution - Chen, Wei‐Liang; Lo, Chao‐Yuan; Huang, Yu‐Chun; Wang, Yu‐Chi; Chen, Wei‐Hung; Lin, Kuan‐Jiuh; Chang, Yu‐Ming (Journal of Raman spectroscopy, 2022)
The strength of SERS signal depends on the amount of analyte adsorbed onto the hotspots of a SERS substrate immersed in solution. This adsorption is a dynamic process and can be described by the Langmuir adsorption model, in which the adsorption is influenced by several factors such as the temperature and the immersion time. By varying the immersion time and immersion volume of a gold nanostructure array SERS substrate in malachite green solution, we find that the required immersion time to reach the equilibrium adsorption coverage increases with decreasing analyte concentration and volume. For a 6.5 mm × 6.5 mm SERS substrate immersed in 15 ml of 1.5 ppb malachite solution, it takes more than 7 days of immersion time for it to reach 63% of the equilibrium coverage in ambient environment. Furthermore, at low concentration and immersion volume, the solution concentration decreases during the adsorption process and causes deviation from the prediction of Langmuir isotherm. In this work, we demonstrate that for quantitative SERS measurement in low analyte concentration, it is critical to take the immersion volume and time into consideration and ensure the equilibrium adsorption coverage or SERS intensity is reached for accurate concentration determination. The strength of SERS signal depends on the amount of analyte adsorbed onto the hotspots of a SERS substrate immersed in solution. This adsorption is a dynamic process and can be described by the Langmuir adsorption model. We demonstrate that for low analyte concentration and immersion volume, the time to reach equilibrium adsorption coverage can take many days and deviates from the Langmuir model prediction. It is therefore critical to take the immersion volume and time into consideration for quantitative SERS determination.